Developing Speaking Skill of Ix Grade Students at Junior High School Through Cake Application - Elma, Elma Alvionita; Mashuri; Mochtar Marhum; Mawardin. M Said (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
An Android app called Cake is dedicated to teaching English. Another option for teaching speaking English is to use cake applications. Because this program is entirely free, there are a lot of benefits. It is not possible to practice speaking, reading, or even listening abilities with this application. The purpose of this study is to determine whether speaking skills of students in SMP Negeri 1Siniu class IX before and after using the cake application were significantly influenced. Quantitative research is used in this study. With a single group pre- and post-test designs, this research design is pre-experimental. This study was conducted in SMP Negeri 1 Siniu in June 2024. The researcher employed spoken monologues to gauge the students' speaking proficiency in order to gather data. Keywords: Developing speaking skill, Cake Application, Fluency, Appropriacy